Hybrid metaheuristics : 11th International Workshop, HM 2019, Concepción, Chile, January 16-18, 2019, Proceedings /: 11th International Workshop, HM 2019, Concepción, Chile, January 16-18, 2019, Proceedings. (2019) - Unknown
No abstract available